2015
DOI: 10.1682/jrrd.2014.03.0087
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of voluntary opening and voluntary closing prosthetic terminal device

Abstract: Abstract-Body-powered prostheses use a cable-operated system to generate forces and move prosthetic joints. However, this control system can only generate forces in one direction, so current body-powered prehensor designs allow the user either to voluntarily open or voluntarily close the tongs. Both voluntary opening (VO) and voluntary closing (VC) modes of operation have advantages for certain tasks, and many endusers desire a terminal device (TD) that can switch between the two modes. However, such a TD must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…For work with occupational heat exposure, biological or chemical hazards, large weights or widely ranging ambient temperatures, there is no other technology. Development of body-powered technology currently is only conducted by a small number of individuals and groups (e.g., Randall Alley [ 147 , 148 ], Bob Radocy [ 40 , 149 ], Bradley Veatch [ 74 , 150 , 151 ], Dick Plettenburg’s group [ 152 156 ], Aaron Dollar’s group [ 157 ] and John Sensinger’s group [ 158 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For work with occupational heat exposure, biological or chemical hazards, large weights or widely ranging ambient temperatures, there is no other technology. Development of body-powered technology currently is only conducted by a small number of individuals and groups (e.g., Randall Alley [ 147 , 148 ], Bob Radocy [ 40 , 149 ], Bradley Veatch [ 74 , 150 , 151 ], Dick Plettenburg’s group [ 152 156 ], Aaron Dollar’s group [ 157 ] and John Sensinger’s group [ 158 ]).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that optimal usage entailed a relatively frequent switch of terminal devices, most notably between the VC and VO control type. For PDW under such conditions, the next frontier is thus in perfecting the design of body-powered heavy duty devices that contain a switchable VO/VC control [ 151 , 158 ].…”
Section: Discussionmentioning
confidence: 99%
“…This system allows for the translation of the Bowden cable movement into a motor command with a considerable effort reduction compared to commercial BP devices (see Table 3). An upgrade to this system, implemented following the Cybathlon, was the introduction of a switch B between two different modalities with a working principle similar to the one presented in [23]. It is possible to switch between a voluntary opening (VO) and a voluntary closing (VC) mode by pushing the lever.…”
Section: Approachesmentioning
confidence: 99%
“…Many prosthetic devices, while not readily available to all, are highly developed with technological features. The need for low cost and easily made artificial limbs is strong in developing nations, which is one of the reasons for these solutions [6]. This refers to amputated children who develop quickly and need to upgrade their prosthesis devices quickly as the years.…”
Section: Introductionmentioning
confidence: 99%
“…The low knowledge level and narrow experience of the resident medical personnel have not provided the required enabling assistance. Violence, diabetes, polio and the diffuse presence of landmines are considered to be the most common causes of limb damage which eventually lead to amputations in developing countries [6].…”
Section: Introductionmentioning
confidence: 99%